Transformation of Mad’u Religious Behavior in the Era of Digital Disruption: A Da’wah Psychology Analysis Based on Albert Bandura’s Social Learning Theory - Abdul Rahman; Muhammad asirin; Daim; Meity Suryandari (Journal of Education and Learning Sciences, 2026)
The rapid development of digital technology in the era of disruption has significantly transformed social interaction patterns and the religious behavior of mad’u. Social media functions not only as a communication tool but also as a social learning environment that influences religious behavior formation. This study examines how the transformation of religious behavior occurs through social learning mechanisms in the digital environment. The research employs a library research method by analyzing relevant scholarly literature. The findings reveal that religious behavior is shaped through processes of observation, imitation, and social reinforcement, which are intensified by social media exposure. However, the internalization of religious values often remains superficial due to the dominance of entertainment-oriented content and the lack of critical reflection. The study concludes that a da’wah psychology approach based on Social Learning Theory is essential in guiding the transformation of religious behavior toward a more authentic and value-based orientation in the digital era.